(untitled) (Simbiótica. Revista Eletrônica, 2026)
The focus group technique is widely used in research conducted in academic settings, as well as in applied social research. This article synthesizes findings on the use of this technique in applied research, especially those involving diagnosis, monitoring, evaluation, and qualification of public policies. To this end, it draws on the authors’ experience using the technique in applied research. The synthesis presents conceptual definitions and the context of the technique’s emergence; its potential; the limitations of its use in this context; its integration with other techniques; possible variations in its formats; and recommended procedures.